Musa Paradisiaca Extract as a Green Inhibitor for Corrosion of Mild Steel in 0.5 M Sulphuric Acid Solution - Mayanglambam,Ramananda S. (2011)
The effect of extract of Musa paradisiaca on corrosion inhibition of mild steel in aqueous 0.5 M sulphuric acid was investigated by weight loss method, potentiodynamics polarisation technique and electrochemical impedance spectroscopy (EIS). The inhibition efficiency is found to increase with increase in concentration of the extract. Polarization measurement indicates that Musa paradisiaca acts as a mixed- type inhibitor and the inhibition efficiency decreases with rise in temperature. The inhibition is assumed to occur via adsorption of inhibitor molecules on metal surface, which obeys Langmuir adsorption isotherm. The activation energy (Ea) and other thermodynamic parameters for inhibition process were calculated. These thermodynamic parameters indicate a strong interaction between the inhibitor and the mild steel surface. SEM and AFM studies confirmed the adsorption of inhibitor molecules on mild steel surface.